Development of FRAMES (Fatigue Risk Assessment with Medical Advise) Application: Self-Assessment Application for Pilots - Retno Wibawanti; Amilya Agustina; Retno Asti Werdhani (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: Pilots have job characteristics that are at risk of causing fatigue. Since fatigue is not a disease, it is important to manage the risk factors. We developed a self-assessment application to manage the fatigue risk for pilots, including physical activity and sleeping difficulties. This application aims to increase pilots’ awareness as one of the health maintenance measures.Methods: The application was developed in collaboration with Garuda Indonesia Training Centre (GITC) to ensure suitable educational content for pilots. The users were asked to fill in data inquiring about their flight characteristics, the Checklist Individual Strength-20 for fatigue screening, General Physical Activity Questionnaire for physical activity, and Jenkins Sleep Scale for sleep difficulties. Afterward, a recommendation will be given based on the received input.Results: The application was able to screen fatigue risks, physical activities, and sleeping difficulties, and provide recommendations based on the questionnaire that was filled in, all adjusted to the user’s work characteristics. The finalized version was then available for download as an Android-based application for the pilots in GITC.Conclusion: The FRAMES is an Android-based self-assessment application for pilots. With the use of this application, hopefully, fatigue can be detected early in pilots, hence counteract measures may be implemented sooner to mitigate fatigue.